Applicability of the Guggenheim–Anderson–Boer water vapour sorption model for estimation of soil specific surface area. (28th December 2017) - Arthur, E.; Tuller, M.; Moldrup, P.; Greve, M. H.; Knadel, M.; de Jonge, L. W.
Summary: Soil specific surface area (SA) controls fundamental soil processes such as retention of water, ion exchange, and adsorption and release of plant nutrients and contaminants. Conventional methods for determining SA include adsorption of polar or non‐polar fluid molecules with associated advantages and limitations. The Guggenheim–Anderson–Boer (GAB) sorption model accurately characterizes soil water vapour sorption isotherms and is posited as an alternate approach for the determination of SA from water vapour sorption. The present study investigates the GAB model as an alternative to other water sorption‐based modelling approaches to determine SA. Measured water vapour adsorption and desorption isotherms for 321 soil samples were used to parameterize the GAB model, the Brunauer–Emmet–Teller (BET) equation and a film adsorption Tuller–Or (TO) model to estimate SA. For adsorption isotherms, the values of the GAB parameters varied depending on the water activity or relative humidity range of measured data (0.03–0.93 compared with 0.10–0.80), whereas the variation for desorption was minimal. For desorption isotherms, the average water activity value at which the GAB monolayer parameter was obtained was 0.24 for kaolinite‐rich samples, 0.31 for illite‐rich or mixed clay samples, 0.34 for smectitic samples and 0.30 for organic matter‐rich samples, respectively. The GAB model provided reasonable estimates of SA (root mean squared error from 11.6 to 36.4 m 2 g −1 ), in particular for smectite‐rich soil samples, when compared with SA measured by the ethylene glycol monoethyl ether (EGME) method. For kaolinitic samples, however, the BET equation provided the best estimate of EGME‐SA. The SA estimates of the GAB model were comparable to those obtained by the TO adsorption model. Thus, the GAB model provides a good alternative to the TO model (applicable only to adsorption data) or the BET model, which fails when the fraction of swelling clay minerals increases. Highlights: GAB, BET and film adsorption models were parameterized with water vapour sorption data. Water activity at GAB monolayer coverage depended on clay mineralogy. Soil organic matter did not affect water activity at monolayer coverage. Estimates of SA from GAB were in accord with EGME‐measured SA.